Homicides in children and adolescents in Southeast Mexico, between 2000 and 2017 - Miranda Juarez, Sarai; Evangelista García, Angélica Aremy (Población y Salud en Mesoamérica, 2021)
Introduction: Mexico is currently facing a context of raising violence that includes the increase of homicides and feminicides in the nation-wide territory. The existent studies present certain gaps regarding regional and age groups information. In particular, those gaps are relevant for population from 0 to 17 years old. That is why this article aims to describe the mortality impacts by means of homicides among that age group in Southeast Mexico. This region is one of the most abandoned in terms of Human Rights and Social Well-Being. Methodology: The article uses the general mortality statistics of the National Institute of Statistics and Geography to calculate the gross mortality rates as well as the specific rates by age and sex groups from 2000 to 2017. Likewise, the average years of life lost are calculated. The study is descriptive and analyzes the impact of homicides within the trend of mortality and life expectancy. Results: A main result shows to the highest percentage of homicides occur among men. However, in terms of the average number of YLL and for the age group 12 to 17 years the largest increases occur among adolescent women. Conclusions: The Southeast region of Mexico presents heterogeneous behavior in homicide mortality rates for the age group 0 to 17 years, highlights the validity and increase of lethal violence against girls, boys and particularly adolescents.